2011
DOI: 10.1371/journal.pone.0017526
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Influences on Morphogenesis of the Knee Joint Revealed through Morphological, Molecular and Computational Analysis of Immobilised Embryos

Abstract: Very little is known about the regulation of morphogenesis in synovial joints. Mechanical forces generated from muscle contractions are required for normal development of several aspects of normal skeletogenesis. Here we show that biophysical stimuli generated by muscle contractions impact multiple events during chick knee joint morphogenesis influencing differential growth of the skeletal rudiment epiphyses and patterning of the emerging tissues in the joint interzone. Immobilisation of chick embryos was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(158 citation statements)
references
References 94 publications
7
150
0
1
Order By: Relevance
“…The effect of mechanical signals during chondrogenesis Studies of paralyzed chick and mouse embryos have revealed that various cartilaginous skeletal elements were shorter and bone eminences were significantly smaller (Hamburger and Waugh, 1940;Hosseini and Hogg, 1991;Rot-Nikcevic et al, 2006;Blitz et al, 2009;Nowlan et al, 2010), and that the size of the proliferative zone (and number of proliferating chondrocytes) in the growth plates of long bones is reduced relative to control embryos (Germiller and Goldstein, 1997;Roddy et al, 2011). Further support for the involvement of mechanical stimulation in chondrocyte proliferation is provided by a study in which cyclic mechanical stimulation of rabbit premaxillae accelerated the rate of chondrocyte proliferation (Wang and Mao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mechanical signals during chondrogenesis Studies of paralyzed chick and mouse embryos have revealed that various cartilaginous skeletal elements were shorter and bone eminences were significantly smaller (Hamburger and Waugh, 1940;Hosseini and Hogg, 1991;Rot-Nikcevic et al, 2006;Blitz et al, 2009;Nowlan et al, 2010), and that the size of the proliferative zone (and number of proliferating chondrocytes) in the growth plates of long bones is reduced relative to control embryos (Germiller and Goldstein, 1997;Roddy et al, 2011). Further support for the involvement of mechanical stimulation in chondrocyte proliferation is provided by a study in which cyclic mechanical stimulation of rabbit premaxillae accelerated the rate of chondrocyte proliferation (Wang and Mao, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that application of mechanical stimuli can determine the developmental fate of mesenchymal stem cells (MSCs) [6]. In particular, appropriate physical stimuli are reported to be essential for limb development: synovial joint and articular cartilage formation in chicken and murine embryos require proper mechanical forces by muscle contractions [7,8]. Optimal intermittent biomechanical activation is also essential for cartilage regeneration during osteoarthritis (reviewed by Sun [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Finite Element models have been used to relate the areas of skeletal elements that are under strain with those undergoing bone formation 10 , as well as to map the areas under strain during endochondral ossification and joint morphogenesis 8,12,21 . Other studies have also been able to apply theoretical growth models to replicate changes during joint development 11,12 .…”
Section: Discussionmentioning
confidence: 99%